2017
DOI: 10.1016/j.trsl.2017.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric antigen receptor–engineered natural killer and natural killer T cells for cancer immunotherapy

Abstract: Natural killer (NK) cells of the innate immune system and natural killer T (NKT) cells, which have roles in both the innate and adaptive responses, are unique lymphocyte subsets that have similarities in their functions and phenotypes. Both cell types can rapidly respond to the presence of tumor cells and participate in immune surveillance and anti-tumor immune responses. This has incited interest in the development of novel cancer therapeutics based on NK and NKT cell manipulation. Chimeric antigen receptors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 118 publications
0
51
0
Order By: Relevance
“…In addition, CAR-NK cell immunotherapies (49,50) that include intracellular domains from both CD16 and NKG2D are shown to be effective in eliminating tumors in pre-clinical studies. Through continued success in the pre-clinical stage, a few CAR-NK cell immunotherapies have entered clinical trials as potential therapeutics for cancer patients (51,52). Excitingly, our model predicts that co-stimulation of CD16 and NKG2D activate the network strongly both individually and collectively.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CAR-NK cell immunotherapies (49,50) that include intracellular domains from both CD16 and NKG2D are shown to be effective in eliminating tumors in pre-clinical studies. Through continued success in the pre-clinical stage, a few CAR-NK cell immunotherapies have entered clinical trials as potential therapeutics for cancer patients (51,52). Excitingly, our model predicts that co-stimulation of CD16 and NKG2D activate the network strongly both individually and collectively.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, NK cell lines are appealing for CAR cell therapy. 5 The continued genetic manipulation of NK cells into antigen-specific effector cells could lead to improved responses of unmodified cells; however, key obstacles must be overcome if NK cellbased immunotherapies are to meet their perceived potential. These obstacles include the inability to traffic into solid tumor sites and avoid tumor immunosuppression and the resistance to current gene transfection techniques; culture and expansion techniques that promote the reproducible growth and expansion of NK cells for therapy must also be developed.…”
Section: To the Editormentioning
confidence: 99%
“…demonstrated to respond as innate cells and as memory-like cells, thereby bridging the innate and adaptive immune responses. 3 In contrast to T cells that recognize peptide antigens presented on major histocompatibility complex (MHC) class I and II, NKT cells recognize lipid antigens presented by CD1d, a MHC class 1-like molecule that can be found on antigen-presenting cells. [4][5][6] NKT cells were demonstrated to have potent antitumor activity in preclinical trials.…”
Section: Nkt Cells Represent a Specific Subset Of T Cells And Have Beenmentioning
confidence: 99%
“…33 Through rapid secretion of various Th1 and Th2 cytokines upon activation, type I NKT cells can activate innate and adaptive immune cells and enhance the antitumor response. 3,34 Therefore, the reciprocal activation of type I NKT cells and DCs via CD40-CD40L and CD1d/lipid antigen-TCR interaction and IFNγmediated DC and CD8+ T cell activation appears to be particularly important. 11 Additionally, several studies have shown that type I NKT cells can influence the tumor microenvironment in a way that increases tumor immunity.…”
Section: S Teps Toward the Nk T C Ar Cell Ther Apymentioning
confidence: 99%